1996
DOI: 10.1021/bi961866d
|View full text |Cite
|
Sign up to set email alerts
|

Mannanase A from Pseudomonas fluorescens ssp. cellulosa Is a Retaining Glycosyl Hydrolase in Which E212 and E320 Are the Putative Catalytic Residues

Abstract: Mannanase A (MANA) from Pseudomonas fluorescens, a member of glycosyl hydrolase family 26, was hyperexpressed in Escherichia coli and purified to homogeneity. Analysis of the stereochemical course of mannotetraose hydrolysis by purified MANA showed that the configuration of the anomeric carbon was retained on cleavage of the middle glycosidic bond. These data suggest that the mannanase hydrolyzes mannooligosaccharides by a double-displacement general acid-base mechanism. By hydrophobic cluster analysis (HCA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 42 publications
3
65
0
Order By: Relevance
“…For example, some of the pectinases may not have attacked the dyed substrates, the pectinase genes are not expressed in E. coli, or the polysaccharidase genes are not represented in the gene library, as they are lethal to the enteric bacterium. This last possibility is consistent with the observation that the high-level expression of several P. cellulosa glycoside hydrolases is lethal to E. coli, due to inefficient secretion [17,30,31].…”
Section: Discussionsupporting
confidence: 91%
“…For example, some of the pectinases may not have attacked the dyed substrates, the pectinase genes are not expressed in E. coli, or the polysaccharidase genes are not represented in the gene library, as they are lethal to the enteric bacterium. This last possibility is consistent with the observation that the high-level expression of several P. cellulosa glycoside hydrolases is lethal to E. coli, due to inefficient secretion [17,30,31].…”
Section: Discussionsupporting
confidence: 91%
“…1). Bolam et al (1996) demonstrated that two glutamate residues act as the catalytic nucleophile and acid-base residues. It is widely believed that these residues are highly conserved within members of the same family and sequence homology suggested that E339 and E438 act as the acid-base and nucleophilic residues, respectively, in C. thermocellum Man26A.…”
Section: Isolation Of Manamentioning
confidence: 99%
“…The resultant DNA was then cloned into the BamHI site of pJG5h, and recombinants in which the two regions of xynA were in the same orientation were designated pJG5, and retained for further use. The conditions used in all the PCR reactions were as described previously [25]. The plasmid pJG4 was constructed by subjecting pJG2 to site-directed mutagenesis using the Transformer kit supplied by ClonTech (Heidelberg, Germany).…”
Section: Construction Of Plasmidsmentioning
confidence: 99%